The Influence of E-Service Quality and Service Innovation on User Loyalty in the Livin' By Mandiri Application with User Satisfaction as an Mediating Variable (Study of Livin' By Mandiri Users in Pontianak City) - Aulia, Nurul; Purmono, Bintoro Bagus (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
This study aims to examine and analyze the effect of e-service quality and service innovation on user loyalty with user satisfaction as the intervening variable. The type of research used in this study is causal associative, and data collection techniques are carried out by distributing questionnaires through the Google form application. The population in this study are Livin' by Mandiri users in Pontianak. The sample used was 100 respondents through non-probability sampling technique with a purposive sampling method. The analysis technique used is Path Analysis using SPSS for windows version 26. The results show that e-service quality has a positive and significant effect on user satisfaction, service innovation has a positive and significant effect on user satisfaction, e-service quality has a positive and significant effect on user loyalty, service innovation has a positive and significant effect on user loyalty, user satisfaction has a positive and significant effect on user loyalty, user satisfaction mediates the effect of e-service quality on user loyalty, and user satisfaction mediates the effect of service innovation on user loyalty.